2017
DOI: 10.1007/s00268-017-4287-x
|View full text |Cite
|
Sign up to set email alerts
|

Case–Control Study of Papillary Thyroid Carcinoma on Urinary and Dietary Iodine Status in South Korea

Abstract: Our results indicate that iodine status differs significantly between patients with PTC and healthy controls, suggesting that iodine may be involved in the occurrence of PTC, although the association between iodine levels and BRAF mutational status did not reach statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…A number of epidemiological studies have attempted to elucidate the association between excessive iodine intake and the risk of developing PTC. For example, Lee et al (4) found that the median urinary iodine concentration (UIC) and food frequency questionnaire score in patients with PTC were significantly higher compared with those in healthy control subjects. Zhou et al (5) discovered that UIC was higher in patients with nodular goiter and PTC compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A number of epidemiological studies have attempted to elucidate the association between excessive iodine intake and the risk of developing PTC. For example, Lee et al (4) found that the median urinary iodine concentration (UIC) and food frequency questionnaire score in patients with PTC were significantly higher compared with those in healthy control subjects. Zhou et al (5) discovered that UIC was higher in patients with nodular goiter and PTC compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The present results that the level of urinary iodine was increased during PTC were consisted with the reports from mainly epidemiological studies. Based on this appearance, many observers dogmatically considered that excessive iodine intake induced the incidence of PTC and iodine intake was a risk factor for the disease [7,16,22,[24][25][26]. In fact, there were two issues: one was the ambiguity of urinary iodine and iodine intake, and the other was the confusion of cause-effect relationship.…”
Section: High Urinary Iodine May Be a Specific Characteristic Of Ptcmentioning
confidence: 99%
“…It has been confirmed that iodine excess-induced thyroid dysfunction may lead to benign thyroid disease, such as autoimmune thyroiditis, benign thyroid nodules (BTN), hypothyroidism and hyperthyroidism [3]. But, it remains considerable controversy about the relationship between high iodine intake and thyroid cancers (TC) risk [4][5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
See 2 more Smart Citations